Hot-melt double-sided adhesive tape and preparation process thereof
By using modified magnetic boron nitride in the hot melt tape of lithium batteries, its thermal conductivity is improved, and the problem of low thermal conductivity of existing hot melt tapes is solved, which significantly improves the anti-fall and safety performance of lithium batteries.
Patent Information
- Application Number
- CN202411811598.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-14
AI Technical Summary
The thermal conductivity of existing lithium battery cells and hot melt tape for outer packaging aluminum-plastic film bonding is low, which hinders the rapid loss of heat inside the lithium battery and affects the working efficiency and safety of the battery.
A hot melt double-sided tape is used, and its hot melt adhesive layer is composed of 80-95 parts of matrix resin, 10 parts of tackifying resin and 10-20 parts of modified magnetic boron nitride. The modified magnetic boron nitride is epoxidized. Made by the amino group of magnetic boron nitride and L-phosphatidylethanolamine, the amino group of epoxy group is ring-opened, and arranged in a directional manner under the action of a magnetic field to reduce the interface thermal resistance and improve thermal conductivity.
The hot melt double-sided tape does not have viscosity at room temperature, and it will produce strong adhesion after heating to 60℃ or above and applying pressure, which significantly improves the drop resistance of lithium batteries and enhances the safety of batteries by improving heat dissipation performance. sex.
Smart Images

Figure BDA0005180675690000081 
Figure BDA0005180675690000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of double-sided adhesive tapes, and in particular relates to a hot-melt double-sided adhesive tape and a preparation process thereof. Background Art
[0002] With the continuous advancement of new energy and energy conservation and emission reduction, electric vehicles have developed rapidly, and the corresponding market demand for high-performance lithium batteries has grown rapidly. The drop resistance of lithium batteries determines the stability and safety of lithium batteries. The drop resistance of lithium batteries is mainly determined by the fit between the electrode group and the outer packaging material. If the fit is not good, the electrode group and the outer packaging material will move relative to each other during the movement of the battery. In severe cases, the electrode group will deform and cause a short circuit, which will bring dangers such as fire and explosion. The prior art is to use hot-melt tape to fix lithium battery cells and the inner surface of the outer packaging aluminum-plastic film. For example, Chinese patent application number 202111152122.9 discloses an electrolysis-resistant adhesive for lithium batteries and a double-sided hot-melt tape using the same and a preparation method thereof. The formula of the pressure-sensitive adhesive layer and the adhesive layer are optimized so that the tape does not react with the electrolyte and is not easy to generate bubbles during use. The total thickness of the tape is reduced, thereby improving the safety of the lithium battery. However, the hot-melt adhesive tape is a polymer material with a very low thermal conductivity, which will hinder the rapid dissipation of heat, is not conducive to reducing the temperature inside the lithium battery, and is not conducive to improving the working efficiency and safety of the battery. Summary of the invention
[0003] The purpose of the present invention is to provide a hot-melt double-sided adhesive tape and a preparation process thereof, so as to solve the problem of low thermal conductivity of the hot-melt adhesive tape used for laminating lithium battery cores and outer packaging aluminum-plastic films.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A hot-melt double-sided adhesive tape comprises a hot-melt adhesive layer and a release film, wherein one side of the hot-melt adhesive layer is used for bonding lithium battery cells, and the other side of the hot-melt adhesive layer is used for bonding lithium battery outer packaging materials.
[0006] The thickness of the hot melt adhesive layer is 2-25 um.
[0007] The hot melt adhesive layer is obtained by coating the hot melt adhesive on the release film and then drying it.
[0008] The hot melt adhesive comprises the following raw materials in parts by weight: 80-95 parts of base resin, 10 parts of tackifying resin, and 10-20 parts of modified magnetic boron nitride.
[0009] Further, the modified magnetic boron nitride is prepared by the following steps:
[0010] The epoxidized magnetic boron nitride, L-phosphatidylethanolamine and methanol are uniformly mixed by ultrasonication, reacted at 40-50°C for 30-60 minutes by stirring, washed by centrifugation and dried to obtain modified magnetic boron nitride.
[0011] Furthermore, the usage ratio of epoxidized magnetic boron nitride, L-phosphatidylethanolamine and methanol is 10 g: 2.9-4.8 g: 100-200 mL.
[0012] Further, the epoxide magnetic boron nitride is prepared by the following steps:
[0013] The magnetic boron nitride is added to an ethanol solution, and then 3-(2,3-epoxypropoxy)propyltrimethoxysilane is added, ultrasonicated for 20 minutes, the temperature is 60-80°C, the rotation speed is 300-500r / min, and stirred for 6-8 hours. Then, the solution is centrifuged at 6000-8000r / min, and the precipitate is vacuum dried to obtain epoxidized magnetic boron nitride.
[0014] Furthermore, the usage ratio of magnetic boron nitride, ethanol solution and 3-(2,3-epoxypropoxy)propyltrimethoxysilane is 10g:100mL:0.5-1g, and the mass fraction of ethanol solution is 40-90%.
[0015] Further, magnetic boron nitride is prepared by the following steps:
[0016] Boron nitride nanosheets, ferric acetylacetonate and triethylene glycol were ultrasonically mixed for 3-5 minutes and then transferred to a reactor. Under nitrogen protection, the mixture was reacted at 258°C for 30 minutes. After the reaction was completed, the mixture was cooled to room temperature, anhydrous ethanol was added, and the mixture was centrifuged for washing and dried to obtain magnetic boron nitride.
[0017] Furthermore, the amount ratio of boron nitride nanosheets, ferric acetylacetonate, triethylene glycol and anhydrous ethanol is 100 mg: 50 mg: 25 mL: 40 mL, and ferric acetylacetonate is in situ reduced in a triethylene glycol solution containing boron nitride nanosheets by a liquid phase method to obtain Fe 3 O 4 / BN composite material, namely magnetic boron nitride.
[0018] Further, the matrix resin is at least one of polystyrene-polybutadiene-styrene block copolymer, hydrogenated styrene-polybutadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, hydrogenated styrene-polyisoprene-styrene block copolymer, polyisobutylene and amorphous α-olefin copolymer.
[0019] Furthermore, the matrix resin is a mixture of hydrogenated styrene-polybutadiene-styrene block copolymer (SEBS), polystyrene-polybutadiene-styrene block copolymer (SBS) and polyisobutylene (PI B) in a mass ratio of 3-6:1:2.
[0020] Furthermore, the tackifying resin is at least one of hydrogenated petroleum resin, hydrogenated rosin resin and hydrogenated terpene resin.
[0021] Furthermore, the release film is made of polyethylene terephthalate or biaxially oriented polypropylene, and has a thickness of 12-25 um.
[0022] The preparation process of the hot-melt double-sided adhesive tape comprises the following steps:
[0023] The hot melt adhesive raw materials are weighed by weight and added into a stirring tank, and a solvent is added to prepare a hot melt adhesive solution with a solid content of 20-40wt%. The hot melt adhesive solution is coated on one side of the release film, and dried at 110°C for 5-8 minutes under the action of an external uniform magnetic field to obtain a hot melt double-sided adhesive tape.
[0024] Furthermore, the solvent is at least one of toluene, ethyl acetate and butyl acetate.
[0025] Furthermore, the magnetic field strength of the externally applied uniform magnetic field is 5-8T.
[0026] Beneficial effects of the present invention:
[0027] The present invention provides a hot-melt double-sided adhesive tape, wherein the hot-melt adhesive layer is a single-layer structure, and no substrate is arranged between the adhesive layers. No burrs are generated after die-cutting, and there should be no risk of puncturing a diaphragm in a lithium battery. The hot-melt adhesive tape is not sticky at room temperature, and when the temperature is raised to 60°C or above and pressure is applied, the hot-melt adhesive layer can produce very strong adhesion, thereby improving the anti-drop performance of the lithium battery. In addition, the hot-melt adhesive layer contains modified magnetic boron nitride. During the preparation process of the hot-melt adhesive layer, since the modified magnetic boron nitride has magnetism, it is directionally arranged on the surface of a release film under the action of a magnetic field, thereby reducing interfacial thermal resistance, significantly improving the thermal conductivity of the coating, and improving the heat dissipation performance of the lithium battery.
[0028] The modified magnetic boron nitride of the invention is obtained by the ring-opening reaction of epoxidized magnetic boron nitride and L-phosphatidylethanolamine through amino and epoxy groups. The surface of the modified magnetic boron nitride contains alkyl long chains, which give the coating strong hydrophobic and oleophobic properties, thereby improving the electrolytic resistance of the double-sided adhesive tape. The surface of the modified magnetic boron nitride also contains phosphate groups, which have excellent chelating properties for metal ions and can improve the adhesion between the double-sided adhesive tape and the aluminum foil. In addition, the modified magnetic boron nitride also contains nitrogen, phosphorus and silicon flame retardant elements, which play a flame retardant role together with ferroferric oxide and boron nitride, thereby preventing the spread of fire to a certain extent and providing a guarantee for the safety of the battery. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In the present application, the melt index (230°C 2.16kg) of SEBS is 9g / min, the diblock content is 29%, and it is purchased from Kraton Polymers with the model number G1657; the hydrogenated petroleum resin is hydrogenated C9 petroleum resin purchased from Shandong Changyao New Materials Co., Ltd. with the model number CY-F1; the SBS is YH-188 from Baling Petrochemical Company; and the polyisobutylene is a polyisobutylene with the brand number HRD350 and a molecular weight of 35,000 produced by Shandong Hongruida Company.
[0031] Preparation Example 1
[0032] The preparation of modified magnetic boron nitride comprises the following steps:
[0033] 10 g of epoxidized magnetic boron nitride, 2.9 g of L-phosphatidylethanolamine and 100 mL of methanol were ultrasonically mixed, stirred for reaction at 40° C. for 30 min, centrifuged at 6000 r / min, washed with anhydrous ethanol, and dried to obtain modified magnetic boron nitride.
[0034] Epoxide magnetic boron nitride is prepared by the following steps:
[0035] 10 g of magnetic boron nitride was added to 100 mL of 40 wt% ethanol solution, and then 0.5 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane was added. The mixture was ultrasonicated for 20 min at 60 ° C and 300 r / min. The mixture was stirred for 6 h and centrifuged at 6000 r / min. The precipitate was vacuum dried to obtain epoxidized magnetic boron nitride.
[0036] Magnetic boron nitride is made by the following steps:
[0037] 10 g of boron nitride nanosheets, 5 g of ferric acetylacetonate and 2.5 L of triethylene glycol were ultrasonically mixed for 3 min and then transferred to a reactor. Under nitrogen protection, the mixture was reacted at 258 °C for 30 min. After the reaction, the mixture was cooled to room temperature, 4 L of anhydrous ethanol was added, and the mixture was centrifuged for washing and dried to obtain magnetic boron nitride.
[0038] Preparation Example 2
[0039] The preparation of modified magnetic boron nitride comprises the following steps:
[0040] 10 g of epoxidized magnetic boron nitride, 4.8 g of L-phosphatidylethanolamine and 200 mL of methanol were ultrasonically mixed, stirred for reaction at 50° C. for 60 min, centrifuged at 6000 r / min, and washed with anhydrous ethanol to obtain modified magnetic boron nitride.
[0041] Epoxide magnetic boron nitride is prepared by the following steps:
[0042] 10 g of magnetic boron nitride was added to 100 mL of 90 wt% ethanol solution, and then 1 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane was added. The mixture was ultrasonicated for 20 min at 80° C. and 500 r / min. The mixture was stirred for 8 h. The mixture was centrifuged at 8000 r / min. The precipitate was vacuum dried to obtain epoxidized magnetic boron nitride.
[0043] Magnetic boron nitride is made by the following steps:
[0044] 10 g of boron nitride nanosheets, 5 g of ferric acetylacetonate and 2.5 L of triethylene glycol were ultrasonically mixed for 5 min and then transferred to a reactor. Under nitrogen protection, the mixture was reacted at 258 °C for 30 min. After the reaction, the mixture was cooled to room temperature, 4 L of anhydrous ethanol was added, and the mixture was centrifuged for washing and dried to obtain magnetic boron nitride.
[0045] Comparative Example 1
[0046] This comparative example is epoxidized magnetic boron nitride, and the preparation process of epoxidized magnetic boron nitride is the same as that of Preparation Example 1.
[0047] Comparative Example 2
[0048] This comparative example is magnetic boron nitride, and the preparation process of magnetic boron nitride is the same as that of Preparation Example 1.
[0049] Comparative Example 3
[0050] This comparative example is modified boron nitride, and the preparation process is as follows:
[0051] 10 g of boron nitride nanosheets were added to 100 mL of 40 wt% ethanol solution, and then 0.5 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane was added. The solution was ultrasonicated for 20 min at 60 ° C and 300 r / min. The solution was stirred for 6 h and centrifuged at 6000 r / min. The precipitate was vacuum dried to obtain modified boron nitride.
[0052] Example 1
[0053] A hot-melt double-sided adhesive tape comprises a hot-melt adhesive layer and a release film. The hot-melt adhesive layer has a thickness of 2um and is obtained by coating the hot-melt adhesive on the release film and then drying it.
[0054] The hot melt adhesive comprises the following raw materials in parts by weight: 80 parts of base resin, 10 parts of tackifying resin, and 10 parts of modified magnetic boron nitride of Preparation Example 1.
[0055] The matrix resin is a mixture of hydrogenated styrene-polybutadiene-styrene block copolymer (SEBS), polystyrene-polybutadiene-styrene block copolymer (SBS) and polyisobutylene (PIB) in a mass ratio of 3:1:2.
[0056] The material of the release film is polyethylene terephthalate and the thickness is 15um.
[0057] The preparation process of the hot-melt double-sided adhesive tape comprises the following steps:
[0058] The hot melt adhesive raw materials were weighed by weight and added into a stirring tank, and toluene was added to prepare a hot melt adhesive solution with a solid content of 20 wt%. The hot melt adhesive solution was coated on one side of the release film, and dried at 110° C. for 8 min under the action of a magnetic field strength of 5 T and an external uniform magnetic field to obtain a hot melt double-sided adhesive tape.
[0059] Example 2
[0060] A hot-melt double-sided adhesive tape comprises a hot-melt adhesive layer and a release film. The thickness of the hot-melt adhesive layer is 15 um. The hot-melt adhesive layer is obtained by coating the hot-melt adhesive on the release film and then drying it.
[0061] The hot melt adhesive comprises the following raw materials in parts by weight: 90 parts of base resin, 10 parts of tackifying resin, and 15 parts of modified magnetic boron nitride of Preparation Example 2.
[0062] The matrix resin is a mixture of hydrogenated styrene-polybutadiene-styrene block copolymer (SEBS), polystyrene-polybutadiene-styrene block copolymer (SBS) and polyisobutylene (PIB) in a mass ratio of 5:1:2.
[0063] The material of the release film is polyethylene terephthalate and the thickness is 15um.
[0064] The preparation process of the hot-melt double-sided adhesive tape comprises the following steps:
[0065] The hot melt adhesive raw materials were weighed by weight and added into a stirring tank. Ethyl acetate was added to prepare a hot melt adhesive solution with a solid content of 30 wt%. The hot melt adhesive solution was coated on one side of the release film. The film was dried at 110° C. for 7 min under the action of a magnetic field strength of 7 T and an external uniform magnetic field to obtain a hot melt double-sided adhesive tape.
[0066] Example 3
[0067] A hot-melt double-sided adhesive tape comprises a hot-melt adhesive layer and a release film. The thickness of the hot-melt adhesive layer is 25 μm. The hot-melt adhesive layer is obtained by coating the hot-melt adhesive on the release film and then drying it.
[0068] The hot melt adhesive comprises the following raw materials in parts by weight: 95 parts of base resin, 10 parts of tackifying resin, and 20 parts of modified magnetic boron nitride of Preparation Example 2.
[0069] The matrix resin is a mixture of hydrogenated styrene-polybutadiene-styrene block copolymer (SEBS), polystyrene-polybutadiene-styrene block copolymer (SBS) and polyisobutylene (PIB) in a mass ratio of 6:1:2.
[0070] The material of the release film is polyethylene terephthalate and the thickness is 15um.
[0071] The preparation process of the hot-melt double-sided adhesive tape comprises the following steps:
[0072] The hot melt adhesive raw materials were weighed by weight and added into a stirring tank, and butyl acetate was added to prepare a hot melt adhesive solution with a solid content of 40wt%. The hot melt adhesive solution was coated on one side of the release film, and dried at 110°C for 8 minutes under the action of a magnetic field strength of 8T and an external uniform magnetic field to obtain a hot melt double-sided adhesive tape.
[0073] Comparative Example 1
[0074] A hot-melt double-sided adhesive tape, compared with Example 1, the only difference is that the modified magnetic boron nitride in Example 1 is replaced by an equal weight portion of the substance in Control Example 1.
[0075] Comparative Example 2
[0076] A hot-melt double-sided adhesive tape, compared with Example 1, the only difference is that the modified magnetic boron nitride in Example 1 is replaced by an equal weight portion of the substance in Control Example 2.
[0077] Comparative Example 3
[0078] A hot-melt double-sided adhesive tape, compared with Example 1, the only difference is that the modified magnetic boron nitride in Example 1 is replaced by an equal weight portion of the product prepared in Control Example 3.
[0079] Comparative Example 4
[0080] A hot-melt double-sided adhesive tape, compared with Example 1, is different only in that the external uniform magnetic field in the preparation process of the hot-melt double-sided adhesive tape in Example 1 is removed.
[0081] The hot melt double-sided adhesives obtained in Examples 1 to 3 and Comparative Examples 1 to 4 were tested for performance, and the test process was as follows:
[0082] (1) Peel strength test after hot pressing
[0083] The hot melt double-sided adhesive obtained in Examples 1 to 3 and Comparative Examples 1 to 4 was bonded to aluminum foil on one side and to cast polypropylene in the aluminum-plastic film on the other side, and hot pressed at 80° C. for 60 min with a pressure of 0.5 MPa, cooled to room temperature, and subjected to a peel strength test according to the method described in standard GB / T2792-2014;
[0084] (2) Peel strength test after hot pressing and immersion in electrolyte
[0085] The release films in the hot melt double-sided adhesives obtained in Examples 1 to 3 and Comparative Examples 1 to 4 were removed, and then respectively placed in an electrolyte at 85° C. for 6 hours, and then taken out and cooled to room temperature, and a peel strength test was performed according to the method described in standard GB / T 2792-2014; the mass ratio of the electrolyte was as follows: EC / PC / DEC / EP=30 / 10 / 30 / 30, and the mass ratio of 1ML i PF6 lithium salt was calculated as 12.5%;
[0086] (3) Thermal conductivity
[0087] Vertical thermal conductivity: Use a mold to cut a square thermal conductive double-sided tape with a diameter of 30cm×30cm, and place it in the test chamber of the DRH III thermal conductivity tester for testing;
[0088] (4) Flame retardant properties
[0089] Limiting oxygen index test: Tested in accordance with GB / T 10707-2008, sample size is 100×6.5×3mm 3 ;
[0090] The test results are shown in Table 1:
[0091] Table 1
[0092]
[0093]
[0094] It can be seen from the test results in Table 1 that, compared with Comparative Examples 1-4, the hot melt double-sided adhesive obtained in Examples 1-3 has better adhesion, electrolytic resistance, and thermal conductivity and flame retardancy. Specifically, it can be seen from the test results of Example 1 and Comparative Example 4 that the removal of the external magnetic field affects the distribution of the modified magnetic boron nitride, thereby significantly reducing the electrolyte resistance and thermal conductivity of the pressure-sensitive adhesive. It can be seen from the test results of Example 1 and Comparative Example 1 that the introduction of L-phosphatidylethanolamine can significantly improve the electrolytic resistance and flame retardancy of the hot melt pressure-sensitive adhesive. It can be seen from the test results of Example 1 and Comparative Examples 2 and 3 that replacing the modified magnetic boron nitride in this case with magnetic boron nitride or epoxidized boron nitride will cause the electrolyte resistance, thermal conductivity, and flame retardancy of the hot melt double-sided adhesive to decrease to varying degrees.
[0095] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0096] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A hot-melt double-sided adhesive tape, comprising a hot-melt adhesive layer and a release film, characterized in that: The hot melt adhesive layer is obtained by coating the hot melt adhesive on the release film and then drying it; The hot melt adhesive comprises the following raw materials in parts by weight: 80-95 parts of base resin, 10 parts of tackifying resin, and 10-20 parts of modified magnetic boron nitride; Modified magnetic boron nitride is made by the following steps: The epoxidized magnetic boron nitride, L-phosphatidylethanolamine and methanol are uniformly mixed by ultrasonication, reacted at 40-50°C for 30-60 minutes by stirring, washed by centrifugation and dried to obtain modified magnetic boron nitride.
2. A hot-melt double-sided adhesive tape according to claim 1, characterized in that: The usage ratio of epoxidized magnetic boron nitride, L-phosphatidylethanolamine and methanol is 10g:2.9-4.8g:100-200mL.
3. A hot-melt double-sided adhesive tape according to claim 1, characterized in that: Epoxide magnetic boron nitride is prepared by the following steps: The magnetic boron nitride is added to an ethanol solution, and then 3-(2,3-epoxypropoxy)propyltrimethoxysilane is added, ultrasonicated for 20 minutes, the temperature is 60-80°C, stirred for 6-8 hours, centrifuged, and the precipitate is vacuum dried to obtain epoxidized magnetic boron nitride.
4. A hot-melt double-sided adhesive tape according to claim 3, characterized in that: The usage ratio of magnetic boron nitride, ethanol solution and 3-(2,3-epoxypropoxy)propyltrimethoxysilane is 10g:100mL:0.5-1g.
5. A hot-melt double-sided adhesive tape according to claim 3, characterized in that: Magnetic boron nitride is made by the following steps: Boron nitride nanosheets, ferric acetylacetonate and triethylene glycol were ultrasonically mixed for 3-5 minutes and then transferred to a reactor. Under nitrogen protection, the mixture was reacted at 258°C for 30 minutes. After the reaction was completed, the mixture was cooled to room temperature, anhydrous ethanol was added, and the mixture was centrifuged for washing and dried to obtain magnetic boron nitride.
6. A hot-melt double-sided adhesive tape according to claim 5, characterized in that: The dosage ratio of boron nitride nanosheets, ferric acetylacetonate, triethylene glycol and anhydrous ethanol is 100 mg: 50 mg: 25 mL: 40 mL.
7. A hot-melt double-sided adhesive tape according to claim 1, characterized in that: The matrix resin is a mixture of hydrogenated styrene-polybutadiene-styrene block copolymer, polystyrene-polybutadiene-styrene block copolymer and polyisobutylene in a mass ratio of 3-6:1:
2.
8. The hot-melt double-sided adhesive tape according to claim 1, characterized in that: The tackifying resin is at least one of hydrogenated petroleum resin, hydrogenated rosin resin and hydrogenated terpene resin.
9. A process for preparing a hot-melt double-sided adhesive tape according to any one of claims 1 to 8, characterized in that: The following steps are involved: Weigh the hot melt adhesive raw material and add it into a stirring tank, add a solvent to prepare a hot melt adhesive solution with a solid content of 20-40wt%, apply the hot melt adhesive solution on one side of the release film, and dry it at 110°C for 5-8min under the action of an external uniform magnetic field to obtain a hot melt double-sided tape.
10. The process for preparing a hot-melt double-sided adhesive tape according to claim 10, characterized in that: The solvent is at least one of toluene, ethyl acetate and butyl acetate, and the magnetic field strength of the external uniform magnetic field is 5-8T.
Citation Information
Patent Citations
Electrolyte-resistant adhesive for lithium battery, double-sided hot melt adhesive tape using same and preparation method of double-sided hot melt adhesive tape
CN113913138A
Cited By
Solvent-free hot-melt spraying type chemical milling protection glue and preparation method thereof
CN120737775A
Solvent-free hot melt spray chemical milling protective adhesive and its preparation method
CN120737775B